Zero Accident di Dunia Konstruksi Edukasi Keselamatan dan Kesehatan Kerja (K3) Konstruksi Bagi Siswa SMKN 4 Gowa - Sitorus, Mentari S.; Zulfadli Ibrahim; Ivan Fachrul Marsha; Andi Firman Muhibuddin; Indah Nur Afiah (Jurnal Kemitraan Masyarakat, 2025)
The high number of work accidents indicates that the implementation of Occupational Safety and Health (K3) is still not optimal, particularly in the construction industry. Vocational schools (SMK) can foster awareness from an early age through education and training. Students in general are not aware of the potential for workplace accidents yet. K3 education for students from an early age can help provide a beneficial understanding and foster attitudes and habits to apply K3 in their future work environments. The purpose of this program is to provide understanding and basic knowledge of construction K3 to students of SMKN 4 Gowa. The method used to educate students through this K3 learning is lectures and socialization, as well as evaluation through pre-tests and post-tests. Overall, the results show that this K3 education activity helps students in the Building Modeling and Information Design program at SMKN 4 Gowa understand all the topics that were talked about. These include understanding K3 and the Zero Accident goal, the importance of construction K3, potential hazards in construction, methods of hazard identification and risk assessment, risk control, recognizing personal protective equipment, symbols and signs, and learning about work accidents that happen in Indonesia.